2 W.W. Hening, Laws of Va. from First Sess. of Legis. in 1619, at 403 (1823) - (:unkn) unknown (My University, 1676)
Ordered that all persons have liberty to sell arms and ammunition to any of his majesties loyal subjects. Includes "Indians of the Easterne shore" have equal liberty to trade with "our friends and neighbouring Indians."
Keywords: TRANSFER